Comparison of Profile Counting and Diameter Measurement for Estimating the Length Density of Seminiferous Tubules or Epididymal Duct - Xu, Wei; Guo, Yang; Yang, Zheng-Wei (Image Analysis and Stereology, 2024)
Transverse testicular sections are often used for histopathological studies and length of seminiferous tubules in the testis is often estimated by the tubule volume divided by the tubules’ cross-sectional area, with the area being obtained by measuring the (short axial) diameters of the round (or elliptical) tubule profiles. But unbiased stereological length estimation is best based on counting of tubule profiles on isotropic sections. To determine the bias of length estimation with the diameter measurement, (i) transverse sections (methacrylate embedded) were obtained from a testis of each normal mature male Sprague-Dawley rat (10 rats in total) and isotropic sections obtained (with the orientator) from the other testis of the rat, and (ii) the tubule length densities were estimated with both methods of profile counting and diameter measurement. The results demonstrated that the method of diameter measurement on transverse or isotropic sections overestimated the length density by 20%-25% compared with profile counting on isotropic sections, probably mainly because of underestimation of the tubules’ cross-sectional area estimated from the short-axial diameters. Length density of the epididymal duct in the epididymis was also estimated with profile counting in the present study, using transverse and isotropic sections for comparison, and a significant statistical difference was not found between the results obtained with the transverse and isotropic sections.